Does Elite Competition Inhibit Growth and Delay Maturation in Some Gymnasts? Probably Not - Baxter-Jones, A. D.; Maffulli, N.; Mirwald, R. L. (Pediatric Exercise Science, 2003)
Concern over possible growth inhibition effects of competitive sports has been and continues to be a source of much debate in the scientific literature. This is not a new debate. At the beginning of the twentieth century studies in boys, suggested both a stimulatory influence on statural growth and also the potential for negative influences. More recently, concerns with regard to potential harmful effects of training on growth have centered on girls, specifically, growth in female gymnasts. The concerns now being expressed relate to reports that intensive physical training in gymnasts, whose training is initiated at young ages, may delay subsequent growth and maturation, and perhaps even reduce final adult stature. We maintain that no viable evidence is available to support the contention that sports training adversely effect growth. We disagree with those who argue that so called 'catch-up' growth observed after reduced or cessation of training provides compelling evidence that growth is affected. However, before discussing the evidence for and against this argument, it should be pointed out that one common element often overlooked is the natural variations in timing and tempo of maturity status observed within a normal healthy population. To understand fully the studies that are about to be discussed one has to first have a clear understanding of the growth process itself.